Microglia Induce PDGFRB Expression in Glioma Cells to Enhance Their Migratory Capacity - Wallmann, Tatjana (iScience, 2018)
High-grade gliomas (HGGs) are the most aggressive and invasive primary brain tumors. The platelet-derived growth factor (PDGF) signaling pathway drives HGG progression, and enhanced expression of PDGF receptors (PDGFRs) is a well-established aberration in a subset of glioblastomas (GBMs). PDGFRA is expressed in glioma cells, whereas PDGFRB is mostly restricted to the glioma-associated stroma. Here we show that the spatial location of TAMMs correlates with the expansion of a subset of tumor cells that have acquired expression of PDGFRB in both mouse and human low-grade glioma and HCGs. Furthermore, M2-polarized microglia but not bone marrow (BM)-derived macrophages (BMDMs) induced PDGFRB expression in glioma cells and stimulated their migratory capacity. These findings illustrate a heterotypic cross-talk between microglia and glioma cells that may enhance the migratory and invasive capacity of the latter by inducing PDGFRB.